Strategies of prevention of the work-related injuries in physiotherapists - Emilia Mikołajewska (Nofer Institute of Occupational Medicine, 2016)
This manuscript presents the author's attempt to review current knowledge on the prevention of work-related injuries in physiotherapists. The author analyzed the literature data concerning the results of studies published until first half of 2015. The aim of the paper is to present and analyze strategies for prevention of work-related injuries in physiotherapists, based on the literature review. The majority of components of discussed strategies still require to be confirmed by future studies. Med Pr 2016;67(5):673-679